Molecular analysis of iduronate -2- sulfatase gene in Tunisian patients with mucopolysaccharidosis type II - Chkioua Latifa; Khedhiri Souhir; Ferchichi Salima; Tcheng Rémy; Chahed Henda; Froissart Roseline; Vianey-Saban Christine; Laradi Sandrine; Miled Abdelhedi (BMC, 2011)
Abstract Mucopolysaccharidosis type II (MPS II, Hunter syndrome) is X-linked recessive lysosomal storage disorder resulting from the defective activity of the enzyme iduronate-2-sulfatase (IDS). Hunter disease can vary from mild to severe, depending on the level of enzyme deficiency. We report the IDS mutation and polymorphisms causing the Hunter syndrome in patients from one family in Tunisia Patients and methods A preliminary diagnosis was made by qualitative detection of urinary glycosaminoglycans of the suspected MPS II probands. The IDS mutation and polymorphisms were determined on these probands and their family members by amplifying and sequencing each of the exons and intron-exon junctions of IDS gene. Results The studied probands were homoallelic for p.R88P mutation. In addition, three known polymorphisms/sequence variants: IVS3-16 (c.419-16 delT), T214M (c.641C > T), T146T (c.438 C > T), IVS5-87(c.709-87G > A) and one previously unknown: IVS7+38(c.1006+38T > C were identified in the MPS II patients. These are the first Tunisian MPS II patients to be genotyped. Conclusion The identification of these mutation and polymorphisms and their genotype-phenotype correlation should facilitate prenatal diagnosis and counseling for MPS II in Tunisia, where a very high rate of consanguinity exists.